Audit Energi Pada Gedung IV Kantor PT PLN (PERSERO) Wilayah Kalimantan Barat - Malik, Abdul (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstract The method used to make efficient use of energy is energy conservation. Energy conservation is the process of improving energy efficiency or energy savings. Energy audit is a method for calculating the rate of energy consumption of a building. In the energy audit conducted at PT Office Building IV. PLN (Persero) region of Kalimantan Barat, especially the air conditioning system (AC) there is excess usage (load) that is so great. Installed power is 57 OD to 51.171 KW compressor power, while the results of the analysis that has been carried out the actual power used ranges from 37 OD with 33.34 KW compressor power. Keywords Energy Conservation, Energy Audit, Power